CONCEPTUALIZING THE URUGUAYAN EDUCATION SYSTEM FOR MATHEMATICS TEACHER TRAINING: NOTES ON THE URUGUAYAN SYSTEM: ANÁLISIS DEL SISTEMA EDUCATIVO URUGUAYO - Silva, Alexandre da; Guberna, Ana María Casnati (Revista de Ciências Humanas, 2025)
Uruguay’s educational system presents a distinct organizational structure that directly influences teacher education, particularly for Mathematics instructors. This training is primarily coordinated by the Consejo de Formación en Educación (CFE), under the jurisdiction of the Administración Nacional de Educación Pública (ANEP), which is responsible for defining the content and methodologies used in teacher preparation programs. The Uruguayan model emphasizes comprehensive education, integrating theory, practice, and pedagogical elements to meet the country’s social and educational needs. In the field of Mathematics, the adopted model promotes an interdisciplinary and context-based approach, encouraging the development of both technical and pedagogical competencies aligned with the current challenges of education. Innovative and participatory methodologies are strongly encouraged to foster critical thinking and problem-solving skills among future educators. The collaboration between teacher training institutions and practicum schools is another essential element, realized through supervised internships and hands-on activities. This connection allows students to gain real-world experience in school settings, better preparing them to navigate diverse educational environments and situations. Furthermore, the Uruguayan system highlights the importance of continuous professional development, aiming at the ongoing improvement of teachers’ knowledge and practices. It encourages reflective teaching and a commitment to enhancing the quality of education. Thus, the training of Mathematics teachers in Uruguay is characterized by a structured, contextualized process focused on excellence in public education, serving as a model for other countries in the region.